Idet landet forsvinder: Variationer over hjem, flugt og den tyske rigsgrænse i Jenny Erpenbecks Hjemsøgelse (2008) - Teistung, Even (Passage - Tidsskrift for litteratur og kritik, 2022)
In Jenny Erpenbeck’s novel Heimsuchung (2008), the German national border is subject to continual change as the history of the 20th century is played out over the course of 11 main chapters, in which different occupants of a lakeside property move in and out of the narrative. The article examines the national border as struc- turing principle in Erpenbeck’s novel, and the interplay between border, national identity, Heimat and the plight of the refugee.